DEMOCRATIC CONSOLIDATION AND VOTER APATHY IN NIGERIA: DYNAMICS, TRENDS AND IMPLICATIONS - MADUBUEGWU, Chibuike E; AGUDIEGWU, Ogbonna Moses; ONYIA, Vincent O; ODOH, Vincent Onyeayanachi; EGBO, Steve (Socialscientia: Journal of Social Sciences and Humanities, 2020)
Election is an ideal of democracy. And, the participation of people in this democratic process underscores the substance of representative governance beyond symbolism. Sadly, emerging and advanced democracies across the world is today challenged by the unpleasant phenomena of voter apathy. In Nigeria, observations and studies have shown the declivity of voter turnout in recent national and sub-national elections. Acknowledging this factuality, this paper examines the historical dynamics of voter apathy and its causality in Nigeria’s electoral democracy. The methodology of this study is qualitative design where the authors adopted a documentary source and non-participant observation methods of data collection and textual analysis of data and events. It revealed persistence trend of voter apathy sustained by exacerbating conditions with adverse effects on democratic consolidation. The paper whence opines that measures to reverse the trend of voter apathy in Nigeria is streamlined in two dimensional perspectives to strengthen the process of democratic consolidation through voter enthusiasm.